CORRELATION OF INTERLEUKIN-6 (IL-6) LEVEL AND NUMBER OF LYMPHOCYTES IN COVID-19 POSITIVE PATIENTS AT PERSAHABATAN HOSPITAL - Mimah Mulhimah; Dian Rachma Wijayanti; Frida Octavia Purnomo (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2022)
Covid-19 caused by the SARS-CoV-2 virus and is transmitted through droplets. In Covid-19 patients who are critical or have severe symptoms, hypercytokines are often found, which is characterized by an increase in the cytokine Interleukin-6 (IL-6). High levels of IL-6 cytokines can disrupt the immune system, including leukocytes, especially lymphocytes, which are the main system of the immune response. The state of continued inflammation and continuously stimulated lymphocytes will cause the lymphocytes to work too hard. This study aims to determine the relationship of Interleukin-6 (IL-6) with lymphocytes in Covid-19 positive patients. This study is a quantitative research with correlation analysis method using data collection technique by purposive sampling. Furthermore, to analyze, the authors used the Kolmogorov-Smirnov normality test and the Spearman correlation test. The results of the analysis showed a fairly significant correlation between levels of Interleukin-6 (IL-6) and the number of lymphocytes in Covid-19 positive patients.